Comparison of infrared coagulation and rubber band ligation for first and second degree haemorrhoids: a randomised prospective clinical trial. Issue 6375 (30th April 1983) - Templeton, J L; Spence, R A; Kennedy, T L; Parks, T G; Mackenzie, G; Hanna, W A
Abstract : One hundred and thirty seven previously untreated out-patients with first and second degree haemorrhoids were allocated at random to treatment by infrared coagulation (n=66) or rubber band ligation (n=71). Complete follow up was obtained in 122 patients (60 who had undergone infrared coagulation (group 1), and 62 rubber band ligation (group 2)) at periods from three months to one year after completion of treatment. Infrared coagulation produced a satisfactory outcome in 51 patients (85%): 34 were rendered asymptomatic and 17 improved. Rubber band ligation produced a satisfactory outcome in 57 patients (92%): 33 were rendered asymptomatic and 24 improved. Both methods were equally effective in first and second degree haemorrhoids. The incidence of side effects, particularly discomfort, during and after treatment was significantly higher in those treated by rubber band ligation (p less than 0.001). This appeared to be an appreciable deterrent to future patient compliance. The number of patients losing more than 24 hours from work was higher after rubber band ligation than after infrared coagulation. The number of treatments necessary to cure symptoms did not differ significantly between the two methods. Infrared coagulation was significantly faster than rubber band ligation (p less than 0.001). Infrared coagulation is a simple, fast, and effective outpatient method for the treatment of first and second degree haemorrhoids with fewer troublesome side effects and higher patient acceptability than rubber band ligation.